"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis